Double-layer heat conduction material based on interlayer communicated carbon fibers and preparation method of double-layer heat conduction material
By introducing directional arrangement of carbon fibers connected between layers into the double-layer thermal conductivity material, the problem of large interface thermal resistance between existing TIM and heat sink materials is solved, efficient vertical heat conduction is achieved, and the material's heat resistance and mechanical properties are improved.
Patent Information
- Application Number
- CN202411945114.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The interlayer interface resistance between the existing thermal interface material (TIM) and the heat sink material is large, which limits the heat dissipation effect of the device, especially the low thermal conductivity in the vertical direction.
Using a double-layer thermally conductive material based on interlayer communication carbon fibers, the thermal resistance is reduced by forming vertically connected orientation arrangement of carbon fibers between the copper composite layer and the polymer composite layer, and the interface between the copper and carbon material is tightly bonded through microalloy modification.
The thermal conductivity in the vertical direction is significantly improved, reaching about 600~1000W/(m·K), enhancing the material's thermal shock resistance and thermal conductivity, while reducing the expansion coefficient and improving mechanical properties.
Smart Images

Figure CN119753531A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material preparation, and relates to a double-layer heat-conducting material based on interlayer connected carbon fibers and a preparation method thereof. Background Art
[0002] Heat sinks are an important part of thermal management. They are mainly used to quickly export heat generated by heat sources such as chips to ensure the normal operation of core components. In addition to requiring a low thermal expansion coefficient that matches the chip in the direction parallel to the chip plane, heat sink materials also need to have high thermal conductivity in the direction perpendicular to the chip plane. AI chips are the core hardware of the artificial intelligence industry. The global level of AI chip development is still in its infancy. With the outbreak of AI technology, different types of chips play a key role in AI computing, training, and reasoning. Each chip type has its own unique advantages to meet different application scenarios and needs. The development momentum of these AI chips is very rapid, which puts higher requirements on the corresponding heat dissipation system.
[0003] In order to protect the chip and reduce the gap thermal resistance during the packaging process, thermal interface materials (TIM layers) are required. TIM can fill small gaps or defects between surfaces, reduce thermal resistance and improve heat transfer efficiency. TIM exists in many forms, including pastes, pads, liquids, films, etc. For example, CN114410061A, etc., TIM is usually composed of high thermal conductivity fillers in a polymer matrix. Some common matrices include silicone grease, polyurethane, acrylic, etc. Each type of TIM has its advantages and disadvantages, and the best choice of TIM for a specific application depends on factors such as cost, thermal conductivity, ease of use and durability. However, the thermal conductivity of TIM materials is generally much smaller than that of copper-based heat sink materials (such as CN107057286A, CN118271853A, etc.), and since the interface between the two is not wettable, it is inevitable that there will be a large interlayer interface thermal resistance. With the increasing requirements for thermal management of high-power devices such as chips, the interlayer interface thermal resistance between the TIM layer and the TIM and the heat sink material has gradually become a bottleneck for efficient heat dissipation, greatly limiting the overall heat dissipation effect of the device.
[0004] CN112480604A discloses a high thermal conductivity carbon fiber composite material with a laminated hybrid structure and a preparation method thereof, wherein a carbon fiber cloth layer is used as the main body, a graphene solution and a copper-containing solution are sprayed on its surface, a flaky filler heat-conducting network parallel to the carbon fiber cloth layer is constructed in the horizontal direction, and a micro-nano scale sheet-and-ball laminated structure is constructed on the surface of the carbon fiber cloth layer in the vertical direction, and then the carbon fiber cloth layer is layered and a polymer matrix material is injected into it, and finally a high thermal conductivity carbon fiber composite material with a laminated hybrid structure is obtained. This method still belongs to the common scheme, that is, the matrix is infiltrated into the carbon fiber cloth, and the finished product has obvious anisotropy, the horizontal direction is a directional arrangement of carbon fiber cloth, and the vertical direction is a layer of fiber cloth and a layer of matrix stacked. Although there is a sheet-and-ball laminated structure, its thermal conductivity effect is not very good, so that the thermal conductivity is high only in the direction of carbon fiber arrangement, and the thermal conductivity in the vertical direction is still low. However, in actual applications, high thermal conductivity in the vertical direction is required. In addition, when copper-containing solution is sprayed, copper does not bond with carbon materials, and can only conduct heat through physical contact, and the thermal conductivity is not improved. From the fracture picture, it can be seen that copper is only used to fill the gaps, but most of the gaps are filled with polymers. Since there is no bond at the interface of different phases, the material is also not resistant to vibration and is easy to break. After thermal shock, a vacuum layer is easily generated, which reduces the thermal conductivity. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a double-layer thermal conductive material based on interlayer connected carbon fibers and a preparation method thereof. The double-layer composite material greatly reduces the thermal resistance between the heat sink material and the polymer-based TIM layer through the carbon fibers vertically connected between the layers, and significantly improves the thermal conductivity in the vertical direction. In addition, by utilizing micro-alloying modification, the interface between copper and carbon materials is tightly bonded, which not only strengthens the mechanical properties, but also improves the heat shock resistance and thermal conductivity.
[0006] The present invention provides a double-layer thermal conductive material based on interlayer connected carbon fibers, comprising a copper composite layer and a polymer composite layer, wherein a vertically connected double-layer, directionally arranged connected carbon fibers are provided between the copper composite layer and the polymer composite layer, wherein the connected carbon fibers are directionally arranged from the copper composite layer and extend to the polymer composite layer, and the connected carbon fibers are also interconnected with internal carbon fibers in the polymer composite layer.
[0007] Furthermore, the copper composite layer is a CuCrZr / molybdenum / carbon fiber composite material, and the polymer composite layer is a polymer / carbon fiber composite material.
[0008] Furthermore, the CuCrZr / molybdenum / carbon fiber composite material is a CuCrZr matrix in which molybdenum particles with low expansion coefficient and directional high thermal conductivity carbon fibers are uniformly dispersed. The molybdenum particles with low expansion coefficient are added to adjust the overall expansion coefficient, and the copper-carbon interface affinity is improved by adding alloying elements to the copper matrix.
[0009] Furthermore, the high thermal conductivity carbon fiber has a diameter of 2 to 20 microns, a length of 20 to 200 microns, a volume fraction of 5% to 30%, and is oriented in a vertical plane direction; the molybdenum particles have a diameter of 10 to 100 microns and a volume fraction of 40 to 60%.
[0010] The present invention also provides a method for preparing a double-layer thermal conductive material based on interlayer connected carbon fibers, comprising the following steps:
[0011] (1) obtaining the CuCrZr / molybdenum / carbon fiber ingot by a non-contact stirring casting process;
[0012] (2) The carbon fibers are oriented by heat and cold deformation.
[0013] (3) obtaining the CuCrZr / molybdenum / carbon fiber composite material by high and low temperature heat treatment, and obtaining the copper composite layer after cutting;
[0014] (4) preparing the polymer / carbon fiber composite material, then etching the upper surface of the copper composite layer to obtain partially exposed carbon fibers, and then compounding the polymer / carbon fiber composite material onto the etched surface through a spin coating process, and obtaining the double-layer thermal conductive material after curing.
[0015] Furthermore, in step (1), the specific steps are as follows:
[0016] 1) pure Cu, CuCr master alloy and CuZr master alloy are melted and cast to obtain Cu-Cr-Zr master alloy;
[0017] 2) Under vacuum or atmosphere protection, the master alloy is remelted at a remelting temperature of 1200 to 1500 degrees Celsius, the required amount of carbon fiber and molybdenum particles are added, the melt temperature is controlled at 1100 to 1300 degrees Celsius, the stirring speed is controlled at 500 to 2500 rpm, a high-speed vortex is formed in the melt, and the melt stirs and disperses the carbon fiber and molybdenum particles in the form of turbulence;
[0018] 3) After being stirred sufficiently, the melt is quickly cooled to about 900-1000 degrees Celsius, stirring is stopped, and then a temperature gradient is designed from top to bottom to allow the bottom of the ingot to be cooled slowly and preferentially until it is completely cooled, thereby obtaining the CuCrZr / molybdenum / carbon fiber ingot.
[0019] Furthermore, the step (2) is specifically as follows: firstly, the CuCrZr / molybdenum / carbon fiber ingot is subjected to hot deformation at a temperature of 750 to 950 degrees Celsius with a deformation amount of more than 50%, and then subjected to cold deformation with a deformation amount of more than 50%, so as to ensure the directional arrangement of the carbon fibers.
[0020] Furthermore, the step (3) is specifically to perform high temperature heat treatment at 850-950 degrees Celsius for 4-6 hours under atmosphere protection, and then perform low temperature heat treatment at 350-550 degrees Celsius for 1-5 hours after rapid cooling, and then cool with the furnace.
[0021] Furthermore, the step (4) is specifically as follows: preparing the polymer / carbon fiber composite material by premixing carbon fibers with a volume fraction of 5% to 50% and a certain proportion of a curing agent in a polymer; etching the upper surface of the copper composite layer with a concentrated nitric acid solution, adjusting the etching depth by time, obtaining exposed carbon fibers on the upper surface after etching, and then compounding the polymer / carbon fiber composite material to the etched surface by a spin coating process, designing a spin coating speed according to the thickness of the required polymer layer, and after the spin coating is completed, placing the composite material in a vacuum furnace for curing treatment according to the polymer curing requirements to obtain the double-layer thermal conductive material.
[0022] Furthermore, according to the interface area of the carbon material, corresponding amounts of Cr and Zr elements are added to the copper matrix, with the Cr content ranging from 0.2 to 2 wt.%, and the Zr content ranging from 0.2 to 4 wt.%.
[0023] Before spin coating, 10% to 25% of carbon fiber and a certain proportion of curing agent are pre-mixed in the polymer.
[0024] The total carbon fiber volume fraction in the polymer composite layer is 5% to 50%.
[0025] The polymer surface can be directly combined with the low expansion coefficient chip to play the role of TIM material.
[0026] Compared with the prior art, the beneficial technical effects of the present invention are:
[0027] (1) The obtained double-layer composite material has a high thermal conductivity in the vertical direction. Directly arranged high thermal conductivity carbon fibers are introduced into the copper matrix. These carbon fibers will be oriented in the heat dissipation direction and form an efficient heat conduction network. More importantly, the carbon fibers extend from the copper matrix into the polymer matrix and are also connected with the internal carbon fibers of the polymer matrix, realizing the interlayer continuity of the carbon fiber network, greatly reducing the interlayer thermal resistance, and effectively improving the heat dissipation capacity of the double-layer composite material. The experimental results show that the double-layer composite material has a high thermal conductivity in the orientation direction, which can reach about 600 to 1000 W / (m·K). In addition, by adjusting the carbon fiber content, the thermal conductivity, expansion coefficient and flexibility of the obtained composite material can be effectively adjusted.
[0028] (2) The copper-carbon interface reacts fully, the interface thermal resistance is small, the bonding strength is high, and the thermal conductivity loss after high and low temperature impact is small. The new composite material uses the combined addition of Cr and Zr to achieve the connection at the copper-carbon interface. The Cr and Zr elements will react with the surface carbon atoms of the carbon fiber during the infiltration process and high-temperature heat treatment to form a carbide layer of a certain thickness on the surface of the carbon material. This transition layer can greatly improve the bonding strength of the copper-carbon interface on the one hand, and is also beneficial to the conduction of phonons on the other hand. The combined addition of Cr and Zr is beneficial to the copper-carbon interface bonding, and the thickness and uniformity of this interface layer can be controlled, thereby achieving a series of advantages such as low interface thermal resistance, high interface bonding strength, and resistance to high and low temperature impact.
[0029] (3) The stirring casting process used is to stir the copper alloy in the high viscosity zone in the molten state. The stirring process is accompanied by the interface reaction between the Cr and Zr elements and the carbon material. Combined with the turbulence generated during the stirring process, it can effectively promote the uniform dispersion of carbon materials and molybdenum particles of different sizes in the copper solution. Combined with the previous rapid solidification and the subsequent directional solidification, a composite material ingot with uniform dispersion of carbon materials and molybdenum particles and good alloy casting quality can be obtained. The carbon fiber network with oriented distribution can be obtained by conventional deformation means, thereby providing good thermal conductivity in the heat dissipation direction. The subsequent etching and spin coating processes are also relatively simple and can effectively construct a continuous interlayer thermal conductive network. By adjusting the molybdenum content in the copper matrix, the carbon fiber content in the copper matrix and the polymer and the degree of orientation, a better combination of thermal conductivity and expansion coefficient can be obtained. The preparation method adopted by the present invention is simple, has high preparation efficiency, low cost, low equipment requirements, and can be suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the morphology of the original powder of the carbon fiber described in the present invention (SEM picture).
[0031] Figure 2 The microstructure and element spectrum of the CuCrZr / molybdenum / carbon fiber ingot of the present invention
[0032] Figure 3 This is the microstructure diagram (SEM picture) of the CuCrZr / molybdenum / carbon fiber ingot of the present invention.
[0033] Figure 4 This is a microstructure diagram (SEM picture) of the copper / carbon fiber composite layer after etching according to the present invention. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] Example 1 and Comparative Example 1
[0036] The embodiment of the present invention is a double-layer thermal conductive material based on interlayer connected carbon fibers and a preparation method thereof, comprising the following steps:
[0037] Firstly, a CuCrZr / molybdenum / carbon fiber ingot was prepared by a stirring casting process;
[0038] 1) pure Cu, CuCr master alloy and CuZr master alloy are smelted and cast to obtain Cu-0.5Cr-1Zr master alloy;
[0039] 2) Under vacuum or atmosphere protection, the obtained master alloy is remelted at a remelting temperature of 1400 degrees Celsius, and 10 vol.% carbon fiber (such as Figure 1 As shown, the carbon fiber has an average diameter of 10 microns and a length of 200 microns) and 30 vol.% molybdenum particles (average size 20 microns), the melt temperature is 1250 degrees Celsius, the stirring speed is 2500 rpm, a high-speed vortex is formed in the melt, and the melt stirs and disperses the carbon fiber and the molybdenum particles in the form of turbulence;
[0040] 3) After sufficient stirring, the melt is cooled rapidly to 1100 degrees Celsius, stirring is stopped, and the bottom of the ingot is allowed to cool slowly first until it is completely cooled to obtain a CuCrZr / molybdenum / carbon fiber ingot (such as Figure 2 , 3 shown).
[0041] The ingot is then subjected to hot extrusion with a deformation amount of 75% at a temperature of 900 degrees Celsius and cold rotary forging with a deformation amount of 80%.
[0042] The high and low temperature heat treatment is carried out in an argon protected rapid heating and cooling furnace. The deformed ingot is heated to 900 degrees Celsius for 5 hours and then quickly cooled; then heated to 400 degrees Celsius for 2 hours, cooled with the furnace, and the required copper-carbon fiber composite layer is obtained after cutting.
[0043] Finally, a concentrated nitric acid solution was used to etch the copper-carbon fiber composite layer. The etching depth was adjusted by time, and the etching time was 25 seconds. Figure 4As shown. Then, the carbon fiber / polymer is composited to the etched surface by spin coating process, the rotation speed is 1000rpm, and the polymer is pre-mixed with 10% carbon fiber and curing agent by volume before spin coating. After spin coating, it is placed in a vacuum furnace for curing treatment to obtain the final required double-layer thermal conductive material, in which the polymer layer thickness is 50 microns.
[0044] Its performance data is shown in Table 1.
[0045] Table 1 Performance data of double-layer composite material in Example 1
[0046]
[0047] In contrast, the carbon fiber / polymer was directly composited to the surface of the copper-carbon fiber composite layer by spin coating without surface etching, and its performance data is shown in Table 2.
[0048] Table 2 Performance data of double-layer composite materials in comparative example 1
[0049]
[0050] Example 2 and Comparative Example 2
[0051] The embodiment of the present invention is a double-layer thermal conductive material based on interlayer connected carbon fibers and a preparation method thereof, comprising the following steps:
[0052] Firstly, a CuCrZr / molybdenum / carbon fiber ingot was prepared by a stirring casting process;
[0053] 1) pure Cu, CuCr master alloy and CuZr master alloy are smelted and cast to obtain Cu-0.7Cr-1.4Zr master alloy;
[0054] 2) Under vacuum or atmosphere protection, the obtained master alloy is remelted at a remelting temperature of 1400 degrees Celsius, 25 vol.% of carbon fiber and 50 vol.% of molybdenum particles are added, the melt temperature is 1250 degrees Celsius, the stirring speed is 2500 rpm, a high-speed vortex is formed in the melt, and the melt stirs and disperses the carbon fiber and molybdenum particles in the form of turbulence;
[0055] 3) After being sufficiently stirred, the melt is quickly cooled to 1100 degrees Celsius, stirring is stopped, and the bottom of the ingot is allowed to be cooled slowly first until it is completely cooled to obtain a CuCrZr / molybdenum / carbon fiber ingot.
[0056] The ingot is then subjected to hot extrusion with a deformation of 80%, the extrusion temperature is 900 degrees Celsius, and the cold rotary forging deformation is 80%. The high and low temperature heat treatment is carried out in an argon-protected rapid heating and cooling furnace. The deformed ingot is heated to 900 degrees Celsius for 5 hours, and then quickly cooled; then heated to 400 degrees Celsius for 2 hours, cooled with the furnace, and cut to obtain the required copper-carbon fiber composite layer.
[0057] Finally, a concentrated nitric acid solution was used to etch the upper surface of the copper-carbon fiber composite layer. The etching depth was adjusted by time, and the etching time was 20 seconds. The carbon fiber / polymer was then composited to the etched surface by a spin coating process at a rotation speed of 1500 rpm. Before spin coating, the polymer was pre-mixed with a volume fraction of 20% carbon fiber and a curing agent. After spin coating, it was placed in a vacuum furnace for curing to obtain the final required double-layer thermal conductive material, in which the polymer layer thickness was 48 microns.
[0058] Its performance data is shown in Table 3.
[0059] Table 3 Performance data of double-layer composite material in Example 2
[0060]
[0061] In contrast, the carbon fiber / polymer was directly composited to the surface of the copper-carbon fiber composite layer by spin coating without surface etching, and its performance data is shown in Table 4.
[0062] Table 4 Performance data of double-layer composite materials in comparative example 2
[0063]
Claims
1. A double-layer thermal conductive material based on interlayer connected carbon fibers, characterized in that: The invention comprises a copper composite layer and a polymer composite layer, wherein a vertically connected double layer of directionally arranged connected carbon fibers is provided between the copper composite layer and the polymer composite layer. The connected carbon fibers are directionally arranged from the copper composite layer and extend to the polymer composite layer, and the connected carbon fibers are also interconnected with the internal carbon fibers in the polymer composite layer.
2. A double-layer thermal conductive material based on interlayer connected carbon fibers according to claim 1, characterized in that: The copper composite layer is a CuCrZr / molybdenum / carbon fiber composite material, and the polymer composite layer is a polymer / carbon fiber composite material.
3. A double-layer thermal conductive material based on interlayer connected carbon fibers according to claim 2, characterized in that: The CuCrZr / molybdenum / carbon fiber composite material is a CuCrZr matrix in which molybdenum particles with low expansion coefficient and directionally arranged high thermal conductivity carbon fibers are uniformly dispersed.
4. The double-layer thermal conductive material based on interlayer connected carbon fibers according to claim 3, characterized in that: The high thermal conductivity carbon fiber has a diameter of 2 to 20 microns, a length of 20 to 200 microns, a volume fraction of 5% to 30%, and is oriented along the vertical plane direction; the molybdenum particles have a diameter of 10 to 100 microns and a volume fraction of 40 to 60%.
5. A method for preparing a double-layer thermal conductive material based on interlayer connected carbon fibers according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) obtaining the CuCrZr / molybdenum / carbon fiber ingot by a non-contact stirring casting process; (2) The carbon fibers are oriented by heat and cold deformation. (3) obtaining the CuCrZr / molybdenum / carbon fiber composite material by high and low temperature heat treatment, and obtaining the copper composite layer after cutting; (4) preparing the polymer / carbon fiber composite material, then etching the upper surface of the copper composite layer to obtain partially exposed carbon fibers, and then compounding the polymer / carbon fiber composite material onto the etched surface through a spin coating process, and obtaining the double-layer thermal conductive material after curing.
6. The method for preparing a double-layer thermally conductive material according to claim 5, characterized in that: In the step (1), the specific steps are as follows: 1) Melting pure Cu, CuCr master alloy and CuZr master alloy, and casting to obtain Cu-Cr-Zr master alloy; 2) Under vacuum or atmosphere protection, the master alloy is remelted at a remelting temperature of 1200 to 1500 degrees Celsius, the required amount of carbon fiber and molybdenum particles are added, the melt temperature is controlled at 1100 to 1300 degrees Celsius, the stirring speed is controlled at 500 to 2500 rpm, a high-speed vortex is formed in the melt, and the melt stirs and disperses the carbon fiber and molybdenum particles in the form of turbulence; 3) After being stirred sufficiently, the melt is quickly cooled to about 900-1000 degrees Celsius, stirring is stopped, and then a temperature gradient from top to bottom is designed to allow the bottom of the ingot to be cooled slowly and preferentially until it is completely cooled to obtain the CuCrZr / molybdenum / carbon fiber ingot.
7. The method for preparing a double-layer thermally conductive material according to claim 5, characterized in that: Specifically, the step (2) is to firstly perform hot deformation on the CuCrZr / molybdenum / carbon fiber ingot at a temperature of 750 to 950 degrees Celsius with a deformation amount of more than 50%, and then perform cold deformation with a deformation amount of more than 50% to ensure the directional arrangement of the carbon fibers.
8. The method for preparing a double-layer thermally conductive material according to claim 5, characterized in that: The step (3) specifically comprises: performing high temperature heat treatment at 850-950 degrees Celsius for 4-6 hours under atmosphere protection, rapidly cooling, performing low temperature heat treatment at 350-550 degrees Celsius for 1-5 hours, and cooling with the furnace.
9. The method for preparing a double-layer thermally conductive material according to claim 5, characterized in that: The step (4) specifically comprises preparing the polymer / carbon fiber composite material by premixing carbon fibers with a volume fraction of 5% to 50% and a certain proportion of a curing agent in a polymer; etching the upper surface of the copper composite layer with a concentrated nitric acid solution, adjusting the etching depth by time, obtaining exposed carbon fibers on the upper surface after etching, and then compounding the polymer / carbon fiber composite material to the etched surface by a spin coating process, designing a spin coating speed according to the required thickness of the polymer layer, and after the spin coating is completed, placing the composite material in a vacuum furnace for curing treatment according to the polymer curing requirements to obtain the double-layer thermal conductive material.
10. The method for preparing a double-layer thermally conductive material according to claim 6, characterized in that: According to the interface area of the carbon material, corresponding amounts of Cr and Zr elements are added to the copper matrix, with the Cr content ranging from 0.2 to 2 wt.%, and the Zr content ranging from 0.2 to 4 wt.%.
Citation Information
Patent Citations
Composite thermal interface material with high heat conductivity and preparation method thereof
CN107057286A
Thermal interface material with high thermal conductivity and preparation process thereof
CN114410061A
Thermal interface material composition and composite thermal interface material prepared from same
CN118271853A
High thermal conductivity metal-based composite material with hierarchical structure, and preparation method thereof
CN102605208A
High-thermal-conductivity carbon fiber composite material with laminated hybrid structure and preparation method of high-thermal-conductivity carbon fiber composite material
CN112480604A
Cited By
Multi-layer structure arc ablation resistant coating based on quinary composite system, preparation method and application of multi-layer structure arc ablation resistant coating
CN120210813A